Discursive Actor Attribution Analysis: A Tool to Analyze How People Make Sense of the Eurozone Crisis - Roose, Jochen; Kousis, Maria; Sommer, Moritz
A crisis situation is marked by a fundamental questioning of routines, structures and established action patterns. The Eurozone Crisis is clearly a crisis in this sense. Making sense of such a crisis is pressing for a society and difficult at the same time as established interpretations are questioned as well. Analyzing the process of interpreting a crisis is of major importance because the interpretations pave the way to future decisions. At the same time it is a methodological challenge for a standardized approach because researchers cannot rely on already established arguments and interpretive frames. With the discursive actor attribution analysis, we propose a tool to analyze a contentious discourse without relying on established frames. Looking at attributions of responsibility as the backbone of making sense in a political contention we provide a structure for data collection without predefining combinations of arguments and evaluations to which the material is assigned. The discursive actor attribution analysis is based on content analysis tools from social movement studies, i.e. protest event analysis, frame analysis and political claim analysis, and analysis of responsibility attribution. It forms a new approach which has the advantage of including many of the merits of the aforementioned perspectives but does not rely on predefined argumentative structures. The paper introduces the discursive actor attribution analysis with reference to existing approaches and reports on some experiences in its application in a Greek-German project on analyzing the discourse on the Eurozone crisis.
Keywords: crisis; political sociology; Greece; Germany; Discursive Actor Attribution Analysis; research method; content analysis